Investigation of multi-stage forward osmosis membrane process for concentrating high-osmotic acrylamide solution - Hao, Shuang; Zhang, Zhaoqian; Zhao, Xin; An, Xiaochan; Hu, Yunxia (Frontiers in Membrane Science and Technology, 2024)
Acrylamide is an important chemical with a huge amount of the global demand for the synthesis of polyacrylamide. A facile and benign approach of concentrating high osmotic acrylamide aqueous solution at a low temperature is needed to replace the current energy-intensive and cost-expensive thermal flash evaporation process. For the first time, a multi-stage forward osmosis (FO) process was developed to concentrate acrylamide solution from 200 g/L to 600 g/L. Thin-film composite (TFC) membrane was fabricated and used for the multi-stage FO process. Acrylamide feed solution (FS) with various concentrations were systematically characterized in terms of viscosity and osmotic pressure (OP). Draw solutes including NaCl and MgCl2 were tested, and their reverse salt fluxes were measured with the quantification of their accumulative contents in the resultant concentrated acrylamide solution. Different operation modes including AL-FS (active layer facing FS) and the AL-DS (active layer facing DS) were also explored to optimize the system efficiency of the FO concentration process. Both single-and multi-stage FO operations were investigated, and their performances were quantified to assess the efficiency of the concentration of acrylamide solution. Results prove that the multi-stage FO operation could dramatically improve the system efficiency for the concentration of acrylamide solution as a comparison with the single-stage FO process, and the draw concentration renewal at stage II, stage III, and stage IV led to a water flux increase by 18.56%, 17.52% and 18.43%, respectively. Moreover, the accumulated MgCl2 in the final 600 g/L acrylamide solution was below 3.7 g/L, less than 0.62 wt.% impurity in the product of acrylamide. Our work provides a practical insight on the viability and optimization of multi-stage FO process for concentrating high osmotic chemicals.